2017
DOI: 10.1176/appi.ps.201700070
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing Psychiatric Medications: A Survey of Long-Term Users

Abstract: Discontinuing psychiatric medication appears to be a complicated and difficult process, although most respondents reported satisfaction with their decision. Future research should guide health care systems and providers to better support patient choice and self-determination regarding the use and discontinuation of psychiatric medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
(32 reference statements)
1
29
0
1
Order By: Relevance
“…Compared with Western countries, the rates of ever being admitted to hospital and taking antipsychotic drugs in people with SMI are still very low in rural China. 32,33 Possible reasons may be related to the patients' poor family economic level, lack of knowledge of mental illness and health disparity between rural and urban areas in China (for example most available health resources and services are concentrated in urban-based psychiatric hospitals) . 3,7,21…”
Section: Discussionmentioning
confidence: 99%
“…Compared with Western countries, the rates of ever being admitted to hospital and taking antipsychotic drugs in people with SMI are still very low in rural China. 32,33 Possible reasons may be related to the patients' poor family economic level, lack of knowledge of mental illness and health disparity between rural and urban areas in China (for example most available health resources and services are concentrated in urban-based psychiatric hospitals) . 3,7,21…”
Section: Discussionmentioning
confidence: 99%
“…These trials must educate participants and clinicians and assess motivational and environmental factors that may affect discontinuation. Unsupported drug discontinuations may explain an undetermined amount of distress seen in medicated individuals [51]. Therefore, it may be unethical to discontinue psychotropic drugs from participants in clinical trials unless one is testing explicitly justified, optimally supportive discontinuation methods for willing individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Not attending to the social environment Surveys and first-person accounts of withdrawal difficulties emphasize support from physicians, therapists, and other people in helping discontinue psychotropic drugs taken for years. 80 Looking only at non relapse-prevention RCTs (i.e., 29 RCTs testing strategies to help individuals discontinue from drugs and stay off them, or examining whether drug-free management of certain dependent or institutionalized individuals might be safe, see Table 1), we observed that 12 did acknowledge environmental, attitudinal, or interpersonal factors -but only two formally assessed them. 81,82 This deficit hints at the lack of relevance to real-world circumstances even of discontinuation trials that do not exploit withdrawal difficulties.…”
Section: Describe Withdrawal Symptoms and Syndromesmentioning
confidence: 99%